2012
DOI: 10.1259/bjr/18685881
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous irradiation of the breast and regional lymph nodes in prone position using helical tomotherapy

Abstract: Helical tomotherapy with prone breast positioning can simultaneously cover the breast and regional nodes with acceptable uniformity and can provide reduced mean dose to proximal organs at risk compared with tomotherapy with supine position. The similarity of plan quality to existing data for conventional breast radiotherapy indicates that this planning approach is appropriate, and that the risk of secondary tumour formation should not be significantly greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
10
1
Order By: Relevance
“…Kainz et al [ 19 ] performed a feasibility trial comparing WB + LNI in prone position to previously reported supine tomotherapy plans. In left sided breast cancer, they showed lower heart and contralateral breast doses using the prone position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kainz et al [ 19 ] performed a feasibility trial comparing WB + LNI in prone position to previously reported supine tomotherapy plans. In left sided breast cancer, they showed lower heart and contralateral breast doses using the prone position.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors report dosimetrical data on regional nodal irradiation in prone position [ 18 , 19 ], this indication has not seen the same shift towards prone irradiation as in WBI, and few data are available for clinical implementation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An air space margin of 2 cm is normally applied in breast tissue [ 11 13 ]. However, the PTV contour was defined only inside the breast tissue in TomoTherapy [ 14 , 15 ]. TomoDirect can be used for breast radiation treatment not only because it uses fixed angles, but also because it can include a PTV margin using Flash.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study and other analyses 21 26 demonstrate that when irradiation of any of the axillary lymph-node levels or the IM lymph nodes is required, special attention should be paid to the doses to these target volumes; in most cases, the conventional tangential fields must be modified to meet the dosimetric need. Although prone radiotherapy is traditionally limited to the operated breast, efforts have been made to extend prone radiotherapy to patients who need irradiation of the axillary and supraclavicular lymph-node regions, through the use of conformal radiotherapy, 30 helical tomotherapy, 31 or intensity-modulated radiation therapy. 32 Therefore, in order to maintain the advantages of prone positioning, the target volume could be extended to the lymph nodes; nevertheless, the feasibility and repositioning accuracy of the method need to be investigated.…”
Section: Discussionmentioning
confidence: 99%